The Southern Ocean: Its Involvement in Global Change - Gordon, Arnold L. (1992)
Southern Ocean is the site of considerable water mass formation which cools and ventilates the modern world ocean. At the polar front zone, formation of cool, low salinity water sinks and spreads northward at intermediate depths limiting the downward penetration of the thermocline. Within the seasonal sea ice zone and along the margins of Antarctica, convection injects very cold oxygenated water into the deep and bottom ocean. These conditions developed as Antarctica shifted into its present configuration and grew a persistent glacial ice sheet, about 14 million years ago. The potential of the Southern Ocean to ventilate the deep and bottom ocean layers is related to occurrence of polynyas that form within the winter sea ice cover. Global climate changes would be expected to alter the polynya size and frequency. Under greenhouse-induced warming offshore polynyas may become less common as the static stability of the Southern Ocean mixed layer increases. This would diminish the Southern Ocean's cooling influence on the deep layers of the world ocean, resulting in a warmer deep ocean. The fate of coastal polynyas is less clear. This article is from 'Proceedings of the International Conference on the Role of the Polar Regions in Global Change Held in Fairbanks, Alaska on 11-15 June 1990. Volume 1', AD-A253 027, p249-255. See also Volume 2, AD-A253 028.